A FAMILY PORTRAIT IN NICHOLAS SPARKS’ NOVEL THE LAST SONG - Kanesya Keles; Ceisy N Wuntu; Imelda Lolowang (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
This study aims to describe the family problem as seen in Nicholas Sparks’ novel The Last Song. The Last Song portrayed a relationship that turns bad because of divorce. The purpose of this research is to find out the family problem and the causes in the novel. This research uses a qualitative method because the data is collected in the form of words. The primary source of this research is the novel itself The Last Song written by Nicholas Sparks and the secondary sources are articles, books and journals that are related to this research. The result of this study showed how a family problem could ruin children’s life in any aspect. It is regarded that people have to maintain the family relationship well although people cannot avoid some problems which potentially ruin the family relationship. Broken families have a serious impact on the children who experience it. The cause of the family problem is because of lack of care for family, lack of communication, and cheating.